Improving Cybersecurity Resilience in Indonesian Cloud Infrastructures Through AI‑Based Threat Intelligence - Manase Sahat H Simarangkir (The Eastasouth Journal of Information System and Computer Science, 2025)
The rapid expansion of cloud computing adoption in Indonesia has significantly increased organizational exposure to cyber threats, making cybersecurity resilience a critical strategic priority. This study examines the role of Artificial Intelligence (AI)-based threat intelligence in enhancing cybersecurity resilience within Indonesian cloud infrastructure. Using a quantitative research design, data were collected from 155 respondents consisting of IT managers, cloud engineers, and cybersecurity practitioners through a structured Likert-scale questionnaire. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS 3). The results indicate that AI-based threat intelligence has a significant positive effect on threat detection accuracy and response effectiveness. Both threat detection accuracy and response effectiveness also have significant positive effects on cybersecurity resilience. Furthermore, AI-based threat intelligence directly strengthens cybersecurity resilience and indirectly enhances it through the mediation of threat detection accuracy and response effectiveness. These findings confirm that AI-driven cybersecurity systems play a strategic role in improving adaptive defense capabilities, accelerating incident response, and strengthening organizational resilience in cloud environments. This study provides important implications for policymakers, cloud service providers, and organizations in designing intelligent cybersecurity frameworks to support Indonesia’s sustainable digital transformation.